2020
DOI: 10.1002/celc.202000692
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/Copper Composite Anode Current Collectors Prepared through Electrochemical Polymerization for Lithium‐Ion Batteries

Abstract: Herein, a new type of composite anode with a Cu foil current collector modified with polyaniline (PANI) was prepared (PANI/Cu). SEM manifests that the PANI layer is 1.8 μm thick and composed of PANI particles with a diameter of 50 nm nanometers, which provides a large contact surface area to enhance the strength of adhesion to the electrode material. FTIR and UV/Vis analysis confirmed that the PANI layer existed in the emeraldine (conductive) form. Half‐cells were assembled by using PANI/Cu and bare/Cu (both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The quinone ring of PMC‐3 is slightly weaker than the benzene ring, indicating that PANI is in the medium oxidation state (in the state of emerald salt). Meanwhile, the ratio of the benzene ring to quinone ring of PMC‐3 is close to 1, indicating that the material possesses good electrochemical performances 35 . With increasing deposition time to 500 and 700 s, the peak intensity of benzene ring increased, and the ratio of benzene ring to quinone ring is over 1 (Figure S3a).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The quinone ring of PMC‐3 is slightly weaker than the benzene ring, indicating that PANI is in the medium oxidation state (in the state of emerald salt). Meanwhile, the ratio of the benzene ring to quinone ring of PMC‐3 is close to 1, indicating that the material possesses good electrochemical performances 35 . With increasing deposition time to 500 and 700 s, the peak intensity of benzene ring increased, and the ratio of benzene ring to quinone ring is over 1 (Figure S3a).…”
Section: Resultsmentioning
confidence: 90%
“…Meanwhile, the ratio of the benzene ring to quinone ring of PMC-3 is close to 1, indicating that the material possesses good electrochemical performances. 35 With increasing deposition time to 500 and 700 s, the peak intensity of benzene ring increased, and the ratio of benzene ring to quinone ring is over 1 (Figure S3a). In addition, some small variations in the characteristic peak can be attributed to the interaction between the components of the electrode.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…In addition, the signal that corresponds to polaron-π* transitions within doped quinoid (Q) structure remains with nanocomposites prepared with CVD CNTs, but it disappears with commercial ones, highlighting a better interaction of the composites with the method used in this study. It is also important to recall that under these conditions, the conductive phase of PANI remains unaltered in the UV region after electropolymerization process [ 117 ]. Recent reports of PANI nanocomposites have demonstrated that the shift of optical absorption band maximum depends on the composition of polymerization bulk solution and polymerization process, which in turn modified the appearance of π-π* and polaron π-transitions [ 114 ], but in our case, such displacements were missing.…”
Section: Resultsmentioning
confidence: 99%
“…Copper foil used as negative electrode support and current collector in lithium-ion batteries has been coated with PANI (Zhang et al 2020e). Storage capability and stability were increased, and the cell impedance decreased.…”
Section: Auxiliary Components and Functionsmentioning
confidence: 99%